Holoprosencephaly and sacral agenesis in a fetus with a terminal deletion 7q36-->7qter. - Morichon-Delvallez, N (1993)
We describe here a fetus with holoprosencephaly and signs of caudal deficiency sequence. Chromosome examination showed a de novo balanced reciprocal translocation (7;22) (q36;q11) with loss of the derivative chromosome 22 in 50% of the cells examined. The present report and available published data indicate that the terminal region of the long arm of chromosome 7 contains genes implicated in the development of the central nervous system and the caudal region.